Effect of Application of Ular Tangga Game Media on Cognitive Learning Result of Human Reproductive System - Nisa, Aulia; Djamahar, Refirman; Evriyani, Dian (Biosfer: Jurnal Pendidikan Biologi, 2015)
One of factors effecting biology learning result is a selective learning media. A proper media application will solve problems occurred during the learning process. This research was aimed to find out the effect of application of ular tangga game media on biology learning result of senior high school student on human reproductive system. It was conducted at SMA Negeri 99 Jakarta on April to May 2014 using a quasi-experimental method. Two groups of grade XI student selected by purposive sampling then divided into experimental and control group consisted of 30 students. Ular tangga media and powerpoint applied respectively in experimental and control group. The result of cognitive learning test was statistically tested using t-test with Î± = 0.05. Based on the calculation, it was found that the p value =0.002. Since p < Î±, the H0 was rejected. This result showed that there was an effect of ular tangga media application on Biology learning result of the topic. As the conclusion, ular tangga game media effected cognitive learning result of students at SMA Negeri 99 Jakarta.